DINAMIKA GLOBAL KEBIJAKAN POLITIK LUAR NEGERI INDONESIA PADA MASA PEMERINTAHAN JOKOWI : (STUDI KASUS KONFLIK ISRAEL-PALESTINA) - Agung Catur Saputra; Muhammad Haikal; Rizki, Zahru Latip; Kustiawan (Jurnal Dialektika Politik, 2026)
This article examines how, under President Joko Widodo's leadership, Indonesian foreignpolicy has undergone significant developments, adapting to modern global dynamics.This policy approach emphasizes economic diplomacy, national development, andIndonesia's active role in maintaining regional stability, particularly in the Israeli-Palestinian conflict. Indonesia strengthens the principle of an independent and activeforeign policy, prioritizes multilateral and humanitarian diplomacy, and supports thetwo-state solution as a path to just and permanent peace. Despite facing global anddomestic challenges, including the COVID-19 pandemic, Indonesia continues to strive toenhance its legitimacy and international role through an inclusive and pragmaticstrategy that reflects its moral commitment and national interests. This study usesdescriptive qualitative methods with analysis based on secondary sources to understandthe dynamics of Indonesia's adaptive and constructive foreign policy in addressing globalchallenges and striving for sustainable regional and global peace.